Edukasi Melalui Video Cara Menyikat Gigi dan Kegiatan Sikat Gigi Massal di SD Negeri 060871 Medan Timur Medan Kota Medan - Herlinawati Herlinawati; Ety Sofia Ramadhan; Miranda Gita W (ABDIGI : JURNAL PENGABDIAN MASYARAKAT KESEHATAN GIGI, 2024)
Changing behavior can be implemented through dental health education with various methods and media that are fun, entertaining and attention-grabbing, and can help and accelerate the process of understanding children about material susbstantion, one of the health promotion media is video. Video is one of the teaching message delivery systems where recorded video material is presented with computer control to students who not only hear and see video and sound, but also provide an active response and that response will determine the speed and sequence of presentation. The purpose of this devotion is to know the knowledge, attitudes and actions of brushing the teeth of elementary school students. The method of this community service is to use video media for 72 students of East Medan District public elementary school classes I and II. The result of this community service is that students' knowledge on how to brush their teeth and mouth is getting better, as evidenced by the questions and answers held at the time of evaluation. From the results of the examination of the Debris Index (DI) criteria, it showed an initial change in the bad category of 44 people (61.11%), to 2 people (2.78%). The conclusion of this community service is that the Tri Dharma of Higher Education (community service) activities have been carried out well as planned.